Produção científica: em foco as publicações dos docentes do PPGCI/UFPB - Figueiredo, Helton de Araujo (2012)
Scientific production is an exteriorization way of scientific knowledge and it reaches its summit with its communication once produced knowledge, besides enhancing the area, is socialized. In this context, the research aims at analyzing quantitatively the professors´ production of the Post-graduation Program in Information Science (PPGCI), of the Federal University of Paraíba, from 2007 and 2011, in order to map the production of scientific articles in journals, complete studies and abstracts published in conference proceedings. It is a documental research and quanti-qualitative procedures, for data analysis, were used. The sources of the analysis are the Lattes curricula from the sixteen professors of the Post-graduation Program in Information Science, of the Federal University of Paraíba. A questionnaire was also employed in order to complement information, present in the Lattes curricula, about the professors´ profile and to collect their opinions about production in co-authorship. Data analysis shows that the professors´ production, in the studied period, totalized 418 publications being 178 articles, 192 communications in events and 48 abstracts, which refer to 175 different themes. For such production, there was collaboration of 317 co-authors. Professors, independently from their research line, are used to publish in partnership with their colleagues from the PPGI and other post-graduation programs, with students under their counseling service, master s students and PIBIC scholarship students, among others, taking part either as authors or co-authors. It can be concluded that the production of PPGCI professors was based, in the last five years, on the following aspects: co-authorship production was higher than the individual one; production of communications in events was larger than the article and abstracts one; production related to present issues and those which promote the contact with their colleagues, debates and discussions, such as communications in events. PPGCI professors are favorable to co-authorship production, but they assume that it does not provide high visibility and acknowledgement for the author.